Literature Review of XBRL Implementation in South Korean Financial Reporting: Implications for Sustainable Business Practices - Shafina, Fira; Haykal, Muhamad Afri; Lee, Joseph (PT Global Digital Sains Tekno, 2026)
Purpose: This paper explores the development of accounting information systems (AIS) and the adoption of eXtensible Business Reporting Language (XBRL) in South Korea, with particular attention to their implications for corporate reporting and business sustainability. Method: A qualitative literature review was undertaken, drawing on scholarly articles and institutional reports identified through targeted keywords. The selected sources encompass empirical studies on XBRL implementation in the Korean capital market, research on AIS development in both large firms and SMEs, and recent works that connect AIS quality with sustainability outcomes. Findings: South Korea was among the earliest countries to mandate XBRL-based electronic filing through the DART system. Empirical evidence demonstrates that XBRL adoption reduces information asymmetry, lowers equity financing costs, and shortens reporting delays, especially for early adopters. Moreover, Korean firms are modernizing AIS by integrating cloud computing, big data, and artificial intelligence, which enhances efficiency and organizational performance. In addition, recent studies highlight that high-quality AIS contributes positively to sustainability performance through improved information reliability, user satisfaction, and system utilization. Implication: The convergence of advanced AIS and XBRL reporting establishes a strong digital infrastructure that fosters transparency, accountability, and long-term sustainability. This experience provides valuable insights for other countries, including Indonesia, in developing digital reporting ecosystems. Originality: By synthesizing diverse strands of literature on AIS and XBRL in South Korea and explicitly linking them to sustainability perspectives, this paper offers an integrated analysis that is useful for students, researchers, and policymakers.